Determinant Factors Influencing Earning Management The role of Tax Planning and Financial Performance - Ade Setia Pratama (Journal of Economy, Accounting and Management Science (JEAMS), 2022)
The goal of this study is to find out how sales growth, tax planning, firm size, and profitability affect earnings management in the consumer goods sector. Purposive sampling was used to pick samples. This study used 45 companies as its sample. Sales Growth has a small effect on earnings management, Tax Planning has no effect on earnings management, Firm size has no effect on earnings management, and Profitability has a small effect on earnings management for food and beverage companies on the Indonesian stock exchange in 2018-2021.